Analysis and assessment of various cryptographic techniques based on a variety of features - Rajan, R; G. Murugaboopathi, Dr; C.Parthasarathy, Dr (International Journal of Engineering and Technology, 2018)
Cloud computing process is an IT service invented for providing efficient network, software, hardware, storage, software systems and resource services. Cloud computing delivers service to the customers through a network. The IT and the management services involved in it is taken care by third parties that owns the physical infrastructure involved in the service. Cloud service provides us the ease to access information at any place, any time with minimum cost involved and high reliability, scalability and resilience. Because of these advantages many organizations are converting themselves to cloud. With growing demand it is necessary to consider the confidentiality of information and also secure it from unauthorized users, denial of services, modification, etc. Securing the storage and computation process in cloud is essential to avoid the above threats. Security protocol in cloud is enhanced through cryptographic algorithms to eliminate the various security threats in our work.